HRMexico : human resource management in Mexico : perspectives for scholars and practitioners - Rao, Pramila (International human resource management., 2015)
The main objective of this book is to provide students, scholars, and practitioners a detailed background on the human resource management (HRM) practices in Mexico. This book provides ten distinguishing chapters that focuses on the core functions of HRM in Mexico. The book took almost a year (Oct 2013 to Aug 2014) to complete. Scholarly and institutional databases were diligently searched for relevant articles for each chapter. This book has 27 tables that provide important information on key current concepts. There are two appendices providing valuable information on Mexican staffing practices. This edition has a new chapter that has live interviews with four professionals who have relevant experience in Mexico.There is paucity in obtaining consolidated information on Mexican HRM practices. This book addresses this dearth in the international management literature by providing individual chapters on the different HRM practices adopted in Mexico. This book will be beneficial for practitioners also as each chapter provides an implication section for business leaders.